"Degenerate Art" : The Fate of the Avant-Garde in Nazi Germany - Barron, Stephanie; Guenther, Peter; Hüneke, Andreas; Janda, Annegret; von Lüttichau, Mario-Andreas; Meyer, Michael; Moritz, William; Mosse, George L.; Zuschlag, Christoph; Los Angeles County Museum of Art, Los Angeles; The Art Institute of Chicago (New York : Harry N. Abrams Inc. Publishers, 1991)
Barlach, Ernst ; Beckmann, Max ; Corinth, Lovis ; Derain, André ; Gauguin, Paul ; van Gogh, Vincent ; Heckel, Erich ; Hofer, Karl ; Kokoschka, Oskar ; etc.
"Degenerate Art" : The Fate of the Avant-Garde in Nazi Germany, Los Angeles County Museum of Art, Los Angeles, February 17 - May 12, 1991 ; The Art Institute of Chicago, June 22 - September 8, 1991
boek
Keywords: Duitsland